2009
DOI: 10.1016/j.jacc.2008.09.055
|View full text |Cite
|
Sign up to set email alerts
|

The Pathologic Continuum of Diabetic Vascular Disease

Abstract: Hyperglycemia can promote vascular complications by multiple mechanisms, with formation of advanced glycation endproducts (AGEs) and increased oxidative stress proposed to contribute to both macrovascular and microvascular complications. Many of the earliest pathologic responses to hyperglycemia are manifest in the vascular cells that directly encounter elevated blood glucose levels. In the macrovasculature, these include endothelial cells (ECs) and vascular smooth muscle cells (VSMCs). In the microvasculature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
325
1
13

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 410 publications
(348 citation statements)
references
References 82 publications
9
325
1
13
Order By: Relevance
“…The increased expression of endothelial adhesion molecules is triggered by the excessive production of advanced glycation end products (AGEs) during hyperglycemia [47]. Additionally, AGEs themselves cause an elevated oxidative stress level in endothelial cells [48,49]. In addition, an ischemia study in diabetic rats showed higher numbers of rolling leukocytes in the mesenteric venules [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased expression of endothelial adhesion molecules is triggered by the excessive production of advanced glycation end products (AGEs) during hyperglycemia [47]. Additionally, AGEs themselves cause an elevated oxidative stress level in endothelial cells [48,49]. In addition, an ischemia study in diabetic rats showed higher numbers of rolling leukocytes in the mesenteric venules [50].…”
Section: Discussionmentioning
confidence: 99%
“…Considerably increased differentiation of MSCs to adipocytes may be another reason for the reduced angiogenic capacity [37]. Concerning diabetic microangiopathy the thickening of the basement membrane has to be considered [49].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing blood levels directly contributes to and progresses CHF. AGE can secondarily lead to CHF by a vast array of negative effects on healthy organs [21][22][23][24][25][26][27][28][29][30][31][32]. In summary there are common overlaps in activating regulatory systems and consequences of homeostatic imbalances.…”
Section: Common Pathophysiology Of Heart Failure and Comorbiditiesmentioning
confidence: 99%
“…Difficulties for the NT include bd dosing, hypotensive effects, achieving top dose and reduced quality of life data in some studies. Metoprolol XR, bisoprolol have neutral or negative effects on metabolic profiles, renal blood flow and nocturnal melatonin levels [29]. Of interest is Nebivolol, highly selective with vasodilatory properties through NO potentiation.…”
Section: Beta Blockersmentioning
confidence: 99%
See 1 more Smart Citation